Antimutagenic properties of green tea - Bunkova, R; Marova, I; Nemec, M (Plant foods for human nutrition (Dordrecht, Netherlands), 2005)
In this work biological effects of two common kinds of green tea (Chinese Gunpowder and Japanese Sencha) were analyzed using three independent tests of antimutagenicity: 1) the Ames test with Salmonella typhimurium TA98, 2) cytogenetic analysis of peripheral blood lymphocytes (CAPL), and 3) test with Saccharomyces cerevisiae D7. Tea extracts were allowed to be antimutagenic based on their ability to inhibit the mutagenic effect of standard mutagens. Amounts of (-)catechin and (-)catechin gallate in tea extracts were determined by high performance liquid chromatography on reversed phase (RP-HPLC). Antioxidant capacity was found using total radical-trapping antioxidant parameter (TRAP) method. Extracts from Gunpowder and Sencha exhibited high antimutagenic activity in the Ames test (24.7+/-3.7% and 34.1+/-2, 1% of inhibition without metabolic activation; 74.9+/-1.7% and 62.7+/-4.3% of inhibition with metabolic activation, respectively) as well as in S. cerevisiae D7 test (Gunpowder: 62.7+/-5.7% of Trp convertants inhibition and 52.6+/-5.3% of Ilv revertants inhibition; Sencha: 45.6+/-4.2% of Trp convertants inhibition, 50.0+/-4.8% of Ilv revertants inhibition). In the CAPL method reduced number of abberant cells as well as decreased number of chromosome breaks was observed using both green tea extracts. Antioxidant capacity and antimutagenicity of green tea extracts was higher than activity of tea catechins and flavonoids.
Keywords: Chromatography, High Pressure Liquid; čaj; Mutagenicity Tests; oxidace-redukce; Oxidation-Reduction; Plant Extracts; testy genotoxicity; Biogenic Amines; Tea; mutageny; biogenní aminy; katechin; Mutagens; Antimutagenic Agents; antimutagenní látky; vysokoúčinná kapalinová chromatografie; rostlinné extrakty; Catechin